The role of job satisfaction in strengthening organizational commitment and its implications for employee loyalty - Heri Susanto; Ade Sofyan; Hikmayanti Wulandari (Institute of Computer Science (IOCS), 2026)
The core objective of this study is to analyze the role of job satisfaction in organizational commitment and its impact on employee loyalty. The study adopts a quantitative research approach paired with structural model analysis to test the direct and indirect associations between all variables. Empirical results show that employee loyalty has an R² of 0.825 (strong explanatory power), and job satisfaction has an R² of 0.567 (moderate explanatory power). All links between variables are positive and statistically significant, and job satisfaction can significantly mediate the association between organizational commitment and employee loyalty. Two core path effects are extremely strong, with only the effect of organizational commitment on employee loyalty being moderate. The study ultimately confirms that these two factors are core elements for improving employee loyalty within organizations.